KINETICS OF TUMOR NECROSIS FACTOR ALPHA (TNF-) AND ILTERLEUKIN 1 ALPHA (IL-1) EXPRESSION IN INTESTINAL MUCOSA OF HEALTHY AND WITH ENTEROPATHY YOUNG ALPACAS (VICUGNA PACOS) - Bardález C., Carla (2013)
The aim of this study was to determine by real-time RT-PCR the presence and relative levels of tumor necrosis factor alpha (TNF-a) and interleukin 1 alpha (IL-1a) mRNA expression in intestinal mucosa of healthy and with enteropathy young alpacas (Vicugna pacos) from Cusco, Peru. A total of 71 samples of jejunum from 0 to 45 days old healthy (n=38) and diseased (n=33) alpacas were processed. Total RNA was extracted from samples and to the synthesis of DNA complementary strand (cDNA) by reverse transcription (RT) was done. Subsequently, conventional PCR and real time RT-PCR was conducted. The results showed that 98.6% (70/71) of the samples amplified a specific product of 251 pb for TNF-a and 100% (71/71) of the samples amplified a specific product of 172 pb for IL-1a, evidenced in the agarose gel during electrophoresis. Analysis of dissociation curves determined that: a) the products amplified with the set of primers for TNF-a were specific and had a melting temperature (Tm) between 85.1 and 86 °C, b) the products of IL-1a were specific with a Tm between 78.8 and 79.7 °C. The relative quantification of mRNA during real time RT-PCR using the 2 Delta Delta Ct method (2-rrCt) showed that the expression of both cytokines was significantly higher in diseased than in healthy alpacas (p<0.05). The expression levels of both cytokines showed an increasing trend in the first four weeks and a gradual decline in the fifth and sixth weeks in healthy animals, whereas in diseased animals none association was found between the expression of cytokines and age.